Anesthesiology and Perioperative Science - Liu, Jin.; Ma, Daqing; Xie, Zhongcong; Turan, Alparslan; Chen, Chan.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer.)
Anesthesiology and Perioperative Science (APS) is the official journal launched by Tianfu Society of Anesthesiology (TFSA). It is a quarterly and peer-reviewed (single-blind) Open Access journal that publishes high-quality cutting-edge articles on all aspects of anesthesiology and perioperative science. Except for traditional anesthesiology areas, such as pain, critical care, monitoring, engineering technology, education and nursing etc., this journal emphasizes innovative discoveries based on anesthesiology principles. We will primarily focus on four distinctive sections as follows: 1. Anesthesia and brain health, focusing on the perioperative fragile brain functions, such as the developing and aging brains, and anesthetic therapeutics for the unhealthy brains, such as sleep disorder, depression, anxiety, amyotrophic lateral sclerosis, etc. 2. Anesthesia and perioperative protection of vital organ functions, such as clinical and experimental research in circulation, neurosciences, respiration, etc. 3. Perioperative big data and artificial intelligence, such as information management, database research, machine learning, techniques and major applied fields in artificial intelligence, etc. 4. Anesthesia mechanism and precise anesthesia, such as anesthetics$1 (Bmechanism of action, drug disposition, basic pharmaceutical research of narcotics, precision delivery of anesthetics, novel anesthetic tools, and practice concepts. Research areas covered in the journal include, but are not limited to: Anesthesia Mechanism and Precise anesthesia Anesthesia Technology, Equipment and Monitoring Anesthetic Preclinical and Clinical Pharmacology Anesthetic Therapeutics, Chinese Medicine Ambulatory Anesthesiology Basic, Clinical and Systemic Neuroscience Big Data and Artificial Intelligence Cardiovascular and Thoracic Anesthesia Clinical and Experimental Circulation Critical Care and Resuscitation Education and Continuing Professional Development Geriatric Anesthesia Obstetric Anesthesia Pediatric Anesthesia Regional Anesthesia Pain Medicine Palliative Care and End-of-Life Care Patient Safety Perioperative Medicine Perianesthesia Nursing.s
Keywords: Anesthesiology; Pain medicine; Medicine; Anesthesiology; Pain Medicine; Clinical Medicine